STUDY ON AGE AND GROWTH OF TOR PVTITORA (HAMILTON) AS EVIDENCED BY SCALES - Tandon, K K; Johal, M S (Indian Journal of Fisheries, 2011)
Tor putitora, M evidenced by its scale, is found to have completed 17 years of life at the length 127. 5 cm. The true annuli could be easily decipiiered due to their continuity all around the scale. The phenomenon of growth compenia^HR has also been noticed at different sUges of life history. The growth constant ^ Â« culations have indicated three periods of life, viz., active-growth period (Istto^ Â«th year), slow-growth period (7th to 12th year) and old-age period (13th ’^ 17th year).